High speed rail as urban generator? An analysis of land use change around European stations. Issue 2 (1st February 2022) - Wenner, Fabian; Thierstein, Alain
ABSTRACT: New High-Speed Rail stations are often expected to act as catalysts for regional and local urban and economic development. Accessibility improvements are assumed to increase locational attractiveness for households and companies, motivating municipal decision-makers to allocate land for urban development projects, particularly in the immediate vicinity of new stations. However, most empirical studies call such automatic effects into question, pointing to the importance of additional local factors, such as station location within the urban context. We construct a dataset of 232 stations in 11 countries in Europe to analyse evolving station placement strategies as well as land use changes in the surroundings of High-Speed Rail stations before and after construction. We find that stations close to the existing urban fabric and well connected by complementary regional and local public transport are on average associated with more land use change, while peripheral stations outside of metropolitan regions hardly attract any development.